Religion and Literature, Identity and Individual: Resetting the Muslim-Christian Encounter - Kersten, Carool (Poligrafi, 2020)
In the first two decades of the twenty-first century inter-faith encounters have become a casualty of a paradigm shift in the thinking about the global order from the political-ideological bi-polar worldview of the Cold War era to a multipolar world marred by the prospect of culture wars along civilisational fault lines shaped by religiously-informed identity politics. On the back of 9/11 and other atrocities perpetrated by violent extremists from Muslim backgrounds, in particular relations with Muslims and the Islamic world are coined in binary terms of us-versus-them. Drawing on earlier research on cosmopolitanism, cultural hybridity and liminality, this article examines counter narratives to such modes of dichotomous thinking. It also seeks to shift away from the abstractions of collective religious identity formations to an appreciation of individual interpretations of religion. For that purpose, the article interrogates the notions of cultural schizophrenia, double genealogy and west-eastern affinities developed by philosophers and creative writers, such as Daryush Shayegan, Abdelwahab Meddeb, and Navid Kermani.